The antecedents for effectiveness of automated enforcement system (AES) in Malaysia / Mohd Ramlan Mohd Arshad, Mohd Nazir Rabun and Mohd Azrul Asraf bin Kamarulzaman - Mohd Arshad, Mohd Ramlan; Rabun, Mohd Nazir; Kamarulzaman, Mohd Azrul Asraf (Universiti Teknologi MARA, Sabah, 2022)
This study aims to investigate the antecedents of the effectiveness of the Automated Enforcement System (AES) in Malaysia. Apart from that, the main objective is to identify the relationship between reducing road accidents, human errors, external conditions, government revenue, and the effectiveness of AES implementation in Malaysia. A total of 200 respondents in this study were the drivers who used highways (PLUS) equipped with an AES system. Purposive and convenience sampling techniques were used with a questionnaire as the instrument. Descriptive and inferential statistics conducted are Pearson correlation and multiple regression analyses. The findings show that there is a significant relationship between reducing road accidents, human errors, external conditions, government revenue, and the effectiveness of the AES system. However, regression analysis shows that reducing road accidents was found to be the main antecedent that affected the effectiveness of AES. Hence, various parties such as authorities, non-governmental bodies, and drivers have benefited from the study.